Biogeographic venom variation in Russell’s viper (Daboia russelii) and the preclinical inefficacy of antivenom therapy in snakebite hotspots - Senji Laxme, R. R. (PLoS Negl Trop Dis, 2021)
BACKGROUND: Snakebite in India results in over 58,000 fatalities and a vast number of morbidities annually. The majority of these clinically severe envenomings are attributed to Russell’s viper (Daboia russelii), which has a near pan-India distribution. Unfortunately, despite its medical significance, the influence of biogeography on the composition and potency of venom from disparate D. russelii populations, and the repercussions of venom variation on the neutralisation efficacy of marketed Indian antivenoms, remain elusive. METHODS: Here, we employ an integrative approach comprising proteomic characterisation, biochemical analyses, pharmacological assessment, and venom toxicity profiling to elucidate the influence of varying ecology and environment on the pan-Indian populations of D. russelii. We then conducted in vitro venom recognition experiments and in vivo neutralisation assays to evaluate the efficacy of the commercial Indian antivenoms against the geographically disparate D. russelii populations. FINDINGS: We reveal significant intraspecific variation in the composition, biochemical and pharmacological activities and potencies of D. russelii venoms sourced from five distinct biogeographic zones across India. Contrary to our understanding of the consequences of venom variation on the effectiveness of snakebite therapy, commercial antivenom exhibited surprisingly similar neutralisation potencies against the majority of the investigated populations, with the exception of low preclinical efficacy against the semi-arid population from northern India. However, the ability of Indian antivenoms to counter the severe morbid effects of Daboia envenoming remains to be evaluated. CONCLUSION: The concerning lack of antivenom efficacy against the north Indian population of D. russelii, as well as against two other ‘big four’ snake species in nearby locations, underscores the pressing need to develop pan-India effective antivenoms with improved efficacy in high snakebite burden locales.